DIGITAL BUREAUCRACY AND PUBLIC SECTOR EFFICIENCY: EXPLORING THE TRANSFORMATION OF GOVERNMENT OPERATIONS - Fatolosa Hulu; Rahmat Purbandono H; Suryadi; Izawati Wook (Alqaprint Jatinangor, 2025)
This study explores the evolution of digital bureaucracy as a catalyst for enhancing efficiency within public sector institutions through a comprehensive literature review. Drawing upon recent academic contributions from 2018 to 2024, the paper examines how digital transformation reshapes administrative structures, decision-making processes, and service delivery mechanisms in government operations. The review identifies key factors influencing successful digital bureaucratic implementation, including leadership commitment, regulatory adaptability, technological infrastructure, and human capital readiness. It also highlights the persistent challenges of data governance, resistance to change, and digital inequality that hinder efficiency gains. By synthesizing empirical and theoretical insights, the study demonstrates that digital bureaucracy not only streamlines administrative procedures but also strengthens transparency, accountability, and citizen engagement. The findings underscore the necessity for integrated policy frameworks that align digital innovation with institutional reform. Furthermore, the paper discusses emerging models of digital governance and their implications for sustainable public sector performance. Ultimately, this review contributes to the growing discourse on e-governance by proposing a conceptual understanding of efficiency in digitally enabled bureaucracies.